2020
DOI: 10.3390/cells9020453
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular Vesicles Derived from Induced Pluripotent Stem Cells Promote Renoprotection in Acute Kidney Injury Model

Abstract: Induced pluripotent stem cells (iPSC) have been the focus of several studies due to their wide range of application, including in cellular therapy. The use of iPSC in regenerative medicine is limited by their tumorigenic potential. Extracellular vesicles (EV) derived from stem cells have been shown to support renal recovery after injury. However, no investigation has explored the potential of iPSC-EV in the treatment of kidney diseases. To evaluate this potential, we submitted renal tubule cells to hypoxia-reo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(38 citation statements)
references
References 52 publications
(57 reference statements)
8
30
0
Order By: Relevance
“…The reduced renal brosis was corroborated by a decreased expression of α-SMA staining in the treated groups, suggesting that both cell treatments were able to reduce the brosis associated with end stage kidney disease. In addition, we demonstrated that the hiPSC treatment decreased macrophage CD68+ cells in the renal parenchyma, possibly due to a paracrine antiin ammatory effect [33,35]. Previous studies lend support to the present observation since it has been reported that mouse kidney progenitor-like cells reduce interstitial brosis, glomerular sclerosis, recruitment of macrophages and myo broblasts in the interstitium, as well as the blood pressure levels in 5/6 CKD model [18].…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…The reduced renal brosis was corroborated by a decreased expression of α-SMA staining in the treated groups, suggesting that both cell treatments were able to reduce the brosis associated with end stage kidney disease. In addition, we demonstrated that the hiPSC treatment decreased macrophage CD68+ cells in the renal parenchyma, possibly due to a paracrine antiin ammatory effect [33,35]. Previous studies lend support to the present observation since it has been reported that mouse kidney progenitor-like cells reduce interstitial brosis, glomerular sclerosis, recruitment of macrophages and myo broblasts in the interstitium, as well as the blood pressure levels in 5/6 CKD model [18].…”
Section: Discussionsupporting
confidence: 85%
“…A similar improvement in renal function was also described by some authors using iPSCs and hiPSC-derived renal progenitors [33,34]. The mechanisms underlying this selective bene cial effect of hiPSCs over the RPC could be due to the release of cytokines and renoprotective factors released by this cell type, as previously reported [33,35]. Both iPSC and RPCs reduced the histological damage observed in CKD.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Furthermore, iPSC-EVs have been involved in immune response modulation, with a decrease in infiltrating macrophages, and in inflammation modulation, through macrophage M2 polarization. A modulation of oxidative stress was also observed [203].…”
Section: Induced Pluripotent Stem Cell Derived Evs In Regenerative Mementioning
confidence: 91%
“…Lee and co-workers have already demonstrated that also iPSCs can protect kidney through the induction of an anti-apoptotic, anti-inflammatory and antioxidant response [202]. Collino et al evaluated the protective and regenerative potential of iPSC-EVs in an acute kidney injury model to explore the possibility of their use in kidney regenerative medicine [203]. In their study the authors demonstrated that the main mechanism associated with mitochondria protection.…”
Section: Induced Pluripotent Stem Cell Derived Evs In Regenerative Mementioning
confidence: 99%